Tactical thieves: the process building to the criminal event - Kenny, James F. (Legal and criminological psychology, 2014)
Purpose The process model presented here was developed as part of safety seminars to help participants recognize criminal preferences and tactics. Method The assessing phase of the model identifies circumstances and target characteristics that thieves find favourable. The approaching phase identifies manipulative and deceptive tactics that thieves use to bait, distract, and control their targets. Result Theft is often the end result of a dynamic set of highly visible, purposeful, and progressively aggressive interactions between criminals and their targets. Conclusion While many thieves are highly skilled, individuals can reduce their risk of selection by limiting criminal opportunity and accessibility. Those targets that identify and respond promptly and effectively to criminal approaches may cause the thieves to withdraw.